Standardized image post-processing of cardiovascular magnetic resonance T1-mapping reduces variability and improves accuracy and consistency in myocardial tissue characterization - Carapella, V; Puchta, H; Lukaschuk, E; Marini, C; Werys, K; Neubauer, S; Ferreira, VM; Piechnik, SK (Elsevier, 2019)
Background: Myocardial T1-mapping is increasingly used in multicentre studies and trials. Inconsistent image analysis introduces variability, hinders differentiation of diseases, and results in larger sample sizes. We present a systematic approach to standardize T1-map analysis by human operators to improve accuracy and consistency.